2010
DOI: 10.4314/ajbr.v10i2.50624
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and phytochemical studies on twelve species of Indian medicinal plants

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
193
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(213 citation statements)
references
References 19 publications
16
193
0
4
Order By: Relevance
“…Botanical medicines or phytomedicines refer to the use of seeds, berries, leaves, bark, root or flowers of any plant for medicinal purposes by significant number of people. Knowledge of the chemical constituents of plants is desirable because such information will be value for synthesis of complex chemical substances [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…Botanical medicines or phytomedicines refer to the use of seeds, berries, leaves, bark, root or flowers of any plant for medicinal purposes by significant number of people. Knowledge of the chemical constituents of plants is desirable because such information will be value for synthesis of complex chemical substances [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…With proline-rich protein tannins have been found to form irreversible complexes (Shimada, 2006) resulting in the inhibition of cell protein synthesis. (Parekh and Chanda, 2007) reported that tannins are known to react with proteins to deliver the typical tanning effect which is essential for the treatment of ulcerated or inflamed tissues. Herbs that have tannins as their key components are astringent in nature and are used for treating intestinal disorders such as dysentery and diarrhea (Dharmananda, 2003).Tannins and their derivatives are phenolic compounds considered to be primary antioxidants or free radical scavengers (Barile et al, 2007).…”
Section: Discussion:-mentioning
confidence: 99%
“…The development of bacterial resistance to presently available antibiotics has necessitated the search for new antibacterial agents (Parekh and Chanda, 2007). Therefore there is a need to develop alternative antimicrobial drugs for the treatment of infections obtained from various sources such as metal nanoparticles and medicinal plants.…”
Section: Introductionmentioning
confidence: 99%